PENDAMPINGAN PELAKSANAAN PEMBELAJARAN ENGLISH FOR YOUNG LEARNER BAGI GURU-GURU SEKOLAH DASAR ISLAM TERPADU (SD IT) MATARAM - Arafiq Arafiq; Nur Ahmadi; Atri Dewi Aziz (Jurnal Abdi Insani, 2022)
This community service was conducted based on the increasing demand of English language throughout the world in general, and in west nusatenggara region in specific. The demand of English has influenced school orientation, especially private schools to combine and integrate English in curriculum, SD IT Anak Shaleh is one of the islamic elementary school in west nusatenggara which puts English as a complimentary subject. Therefore, this community service aims at providing assistance for the teachers in the school in for better English instruction so as to make the class always interesting and all students feel like learning in their ways. This community service was done involving thirty-three teachers as participants. With the help of the facilitators, the teachers were asked to discuss about what, where, when, and how they wanted the service to be conducted (planning), actively participate in the assistance provided, acting out in practice teaching (peer teaching), evaluation and feedback. The results of this service generally have met the demands of the participants. However, with the time allotment provided in this service, they wanted to get more that expected before. In the process of conceptualizing theories, simulating methods and approaches, practicing with friends, the participants were very enthusiastic and active. They acted as if they were really teaching their students in normal classes rather than just doing peer teaching. They can execute the lesson plan quite well expect the lack of instructional media and TPACK (technological pedagogical and content knowledge). In conclusion, they community was success to meet the participants (partner) demand. They really have had something new and hope they can apply it to the real class they teach.